(untitled) (Journal of Engineering, 2014)
Ex-situ bioremediation of 2,4-D herbicide-contaminated soil was studied using a slurry bioreactor operate at aerobic conditions. The performance of the slurry bioreactor was tested for three types of soil (sand, sandy loam and clay) contaminated with different concentration of 2,4-D, 200,300and500mg/kg soil. Sewage sludge was used as an inexpensive source of microorganisms which is available in large quantities in wastewater treatment plants. The results show that all biodegradation experiments demonstrated a significant decreases in 2,4-D concentration in the tested soils. The degradation efficiency in the slurry bioreactor decreases as the initial concentration of 2,4-D in the soils increases.A 100 % removal was achieved at initial concentration of 200mg 2,4-D/kg of sandy soil after 12 days and 92 % at 500mg 2,4-D/kg sandy soil after 14 days.Clay soil represented minimum removal efficiency among the three soils, 82 % at initial concentration of 200mg 2,4-D/kg clay soil after 12 days and 72 % for 500mg 2,4-D/kg clay soil after 14 days. Abiotic conditions were performed to investigate the desorption efficiency of the contaminant from soil to liquid phase through the three soils. In abiotic reactor the results showed that the rate of desorption for sand and sandy loam soils were nearly the same, it varied between0.102-0.135 day-1 at different initial concentration of 2,4-D. While for clay soil the desorption rate varied between 0.042- 0.031 day-1 at different initial concentration of 2,4-D. The decrease in desorption rate in clay soil refers to the characteristic of clay soil, (fine texture, high organic matter and high cation exchange capacity compared with the other soils) that may retain the 2,4-D in the organic matter and the clay minerals.